Prevalence and Antimicrobial Resistance of Escherichia coli in Locally Produced Soft Cheese - M. Shekhani, Dawod Noori; Mohammed, Dlsher (American Journal of Botany and Bioengineering, 2026)
The cross-sectional study was conducted to determine the prevalence and antimicrobial resistance profile of Escherichia coli isolates of 100 consignments of local production soft cheeses in Sulaymaniyah, Erbil, Duhok, and Halabja in the months of June-August 2025. There were five types of cheese, including white, feta, local curd, blended soft cheese, and mozzarella. Methodology Isolation and identification of E. coli was done as standard microbiological procedures and the primary culture was done on MacConkey and EMB agar after which biochemical tests were done. Antimicrobial susceptibility testing was performed using the disk diffusion technique according to the Clinical and Laboratory Standards Institute (CLSI) guidelines such as amoxicillin, tetracycline, ciprofloxacin, gentamicin, and chloramphenicol. Results – Prevalence coli was found within 55% of all the cheese samples with the highest prevalence rate in local curd (70%), and white cheese (60%), but with the lowest prevalence in mozzarella (25%). Findings- Antimicrobial Resistance. The amoxicillin (85 03) and tetracycline (70 03) had the highest resistance rates, with chloramphenicol (40 03) coming next. On the other hand ciprofloxacin and gentamicin showed reduced resistance levels (30% each). Ciprofloxacin (65 seriously) and gentamicin (55 -percent) had the most favourable susceptibility. Geographical Variation The level of contamination also differed geographically, with 55 0-25 0 percent in Sulaymaniyah and Duhok, respectively, indicating that there were differences in processing hygiene practices in the different regions studied. Conclusion These results highlight the fact that artisanal soft cheese processed using raw milk is a major source of multidrug-resistant E. coli in the Kurdistan province of Iraq. These statistics demonstrate the essential role of proper pasteurization, establishment of improved deposition measures and the application of better foresight of antibacterial agents at each of the production phases of dairy products to protect the health of the people.